2002
DOI: 10.1093/pcp/pcf077
|View full text |Cite
|
Sign up to set email alerts
|

The ASYMMETRIC LEAVES2 Gene of Arabidopsis thaliana, Required for Formation of a Symmetric Flat Leaf Lamina, Encodes a Member of a Novel Family of Proteins Characterized by Cysteine Repeats and a Leucine Zipper

Abstract: The ASYMMETRIC LEAVES2 (AS2) gene of Arabidopsis thaliana is involved in the establishment of the leaf venation system, which includes the prominent midvein, as well as in the development of a symmetric lamina. The gene product also represses the expression of class 1 knox homeobox genes in leaves. We have characterized the AS2 gene, which appears to encode a novel protein with cysteine repeats (designated the C-motif) and a leucine-zipper-like sequence in the amino-terminal half of the primary sequence. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
481
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(505 citation statements)
references
References 47 publications
22
481
0
2
Order By: Relevance
“…Although the precise molecular mechanism remains unclear, our study clearly demonstrates that LBD transcription factors are key regulators in directing callus formation in a typical in vitro plant regeneration system. In addition, since the LBD family comprises a large number of members in plant genomes, it is likely that other close LBD homologues may also have some effect on callus formation, which might explain why transgenic plants overexpressing Arabidopsis LBD6/AS2 or poplar LBD1 displayed a slightly enhanced callus-forming phenotype [18,26].…”
Section: Lbd Transcription Factors Are Key Regulators To Mediate Callmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise molecular mechanism remains unclear, our study clearly demonstrates that LBD transcription factors are key regulators in directing callus formation in a typical in vitro plant regeneration system. In addition, since the LBD family comprises a large number of members in plant genomes, it is likely that other close LBD homologues may also have some effect on callus formation, which might explain why transgenic plants overexpressing Arabidopsis LBD6/AS2 or poplar LBD1 displayed a slightly enhanced callus-forming phenotype [18,26].…”
Section: Lbd Transcription Factors Are Key Regulators To Mediate Callmentioning
confidence: 99%
“…The LBD family comprises 43 members in Arabidopsis, 35 in rice and 57 in poplar [18][19][20][21]. Functional characterization of several LBD members revealed that LBD genes play critical roles in defining lateral organ boundaries and regulating many aspects of plant development, including root, leaf, inflorescence and embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…AS1 encodes a MYB domain transcription factor related to Antirrhinum PHANTASTICA and maize ROUGH SHEATH2 (Byrne et al, 2000;Schneeberger et al, 1998;Sun et al, 2002;Waites et al, 1998). AS2 encodes a nuclear-localized protein that contains cysteine repeats and a leucine-zipperlike motif (Iwakawa et al, 2002). The as1 and as2 mutations suppress the embryonic and vegetative phenotype of the stm mutant, as as1 stm and as2 stm double mutants form a SAM (Byrne et al, 2000(Byrne et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…; Semiarti et al, 2001;Sun et al, 2002), AS2, which encodes a LOB domain/Leu zipper transcription factor (Iwakawa et al, 2002;Lin et al, 2003), and BLADE-ON-PETIOLE1 (BOP1), recently shown to encode a NONEXPRESSOR OF PR GENES1 (NPR1)-like transcription factor (Ha et al, 2003(Ha et al, , 2004. AS1 and AS2 function in the same genetic pathway and bind to each other in yeast, suggesting that they are members of a complex (Byrne et al, 2002;Iwakawa et al, 2002;Lin et al, 2003;Xu et al, 2003).…”
mentioning
confidence: 99%